The Norton anthology of English literature media companion - Abrams, M. H. (Meyer Howard) 1912-; Greenblatt, Stephen 1943- (Norton, 2003)
Interactive database includes over 250 visual images, over 35 musical selections (more than ninety minutes), over thirty readings and audio performances, maps, glossary of literary terms. Also provides access to Norton topics online and Norton online archive.